2011
DOI: 10.1080/10810730.2011.561912
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mystery Shopper Reports on Age Verification for Tobacco Purchases

Abstract: Mystery shops (MS) involving attempted tobacco purchases by young buyers have been employed to monitor retail stores’ performance in refusing underage sales. Anecdotal evidence suggests that MS visits with immediate feedback to store personnel can improve age verification. This study investigated the impact of monthly and twice-monthly MS reports on age verification. Forty-five Walgreens stores were each visited 20 times by mystery shoppers. The stores were randomly assigned to one of three conditions. Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Procedures to verify that clerks consistently check IDs (eg, 'mystery shoppers' or reward and reminder programs) may be critically important if such policies are to be effective. 38 The importance of store policies is further highlighted by our results showing that visible age-of-sale signs were associated with an increased likelihood that the clerk requested proof of age. Similar findings have been reported regarding the presence of signage sales of alcohol to minors.…”
Section: Discussionmentioning
confidence: 75%
“…Procedures to verify that clerks consistently check IDs (eg, 'mystery shoppers' or reward and reminder programs) may be critically important if such policies are to be effective. 38 The importance of store policies is further highlighted by our results showing that visible age-of-sale signs were associated with an increased likelihood that the clerk requested proof of age. Similar findings have been reported regarding the presence of signage sales of alcohol to minors.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies have found that enforcement of underage sales laws through compliance checks is associated with decreased rates of tobacco sales to youths (18, 19). Similarly, programs that reinforce retailers for not selling tobacco products to minors have been shown to be effective in increasing ID checking rates (20). The effect of reduced underage sales on youths’ cigarette smoking, however, remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Additional reward and reminder visits, held at different times in order to thwart potential alerting of other stores, and with new trained volunteers, should help to further establish the long-term utility of this intervention. Communication between stores may help to reinforce the sense that clerks should be alert to the potential for decoy purchase attempts at any time (12). …”
Section: Discussionmentioning
confidence: 99%
“…In reward and reminder programs, youthful decoys attempt to purchase alcohol and then either “reinforce” clerks who do not sell or provide a “reminder” of the law to clerks who do sell. Such programs, also referred to as “mystery shopper reports” (12), have been shown to significantly reduce tobacco sales to minors and to reduce self-reported smoking and drinking (13). A large randomized community trial on environmental approaches to preventing underage drinking included an effective reward and reminder and compliance program targeting convenience store outlets in 36 small Oregon communities (1417).…”
Section: Introductionmentioning
confidence: 99%